Coordinated expression and assembly of BiP, p58 IPK , and ER chaperone complexes maximize proinsulin folding in pancreatic β cells - Insook Jang; Alec Duffey; Pamela Itkin-Ansari; Peter Arvan; Randal J. Kaufman (Proceedings of the National Academy of Sciences, 2026)
Proper proinsulin folding in the endoplasmic reticulum (ER) is prerequisite to producing bioactive insulin, and proinsulin misfolding causing β cell ER stress accompanies pancreatic β cell dysfunction in type 2 diabetes (T2D). How (and which) ER chaperones coordinate to prevent proinsulin misfolding is largely unknown other than an unspecified dependence on the hsp70 member, BiP. A genetically engineered mouse enables efficient, specific pulldown of endogenous islet β cell BiP (GRP78, the major HSP70 ER chaperone) in complexes with client proteins. We demonstrate that BiP assembles in various protein complexes (including cochaperones p58 IPK , GRP170, ERdj3, and oxidoreductases PDIA1 and PDIA6) that specifically bind to nonnative proinsulin. BiP requires p58 IPK for productive proinsulin folding, whereas nonstoichiometric BiP excess actually hinders proinsulin folding. Coordinated and dyscoordinated BiP/cochaperone assembly in response to demand for proinsulin highlights physiologic and pathophysiologic conditions, respectively, offering a potential check point for therapeutic intervention.